Backbone tree for Chaetothyriales with four new species of Minimelanolocus from aquatic habitats. Issue 11 (November 2015) - Liu, Xiao-Ying; Udayanga, Dhanushka; Luo, Zong-Long; Chen, Li-Jiao; Zhou, De-Qun; Su, Hong Yan; Hyde, Kevin D.
Abstract: We are studying the freshwater lignicolous fungi along a north-south latitudinal gradient in Asia. In this paper, fresh collections of Minimelanolocus from submerged wood in streams in Yunnan Province, China are characterised based on morphology and molecular phylogeny based on three rDNA regions: 18S (SSU), ITS1-5.8S-ITS2 (ITS) and 28S nuclear rDNA (LSU). The phylogenetic analysis of combined LSU and SSU sequence data and a separate analysis of ITS placed the isolates within the family Herpotrichiellaceae, order Chaetothyriales . An updated phylogenetic backbone tree for Chaetothyriales is provided with available ex-type and additional isolates. One of the isolates collected was identified as Minimelanolocus obscurus based on morphology and molecular data. Minimelanolocus aquaticus, M. asiaticus, M. curvatus and M . melanicus are described as new species considering the interspecific ITS variability and morphology. The phylogenetic placement of Minimelanolocus in Chaetothyriales is novel and provides new sequence data for the genus as a distinct lineage in Chaetothyriales . The conidial characters of all the known species in the genus are summarized. Descriptions and illustrations are provided for the five species of Minimelanolocus with notes on their taxonomy and phylogeny. Highlights: Molecular data and morphology are used to characterize fresh collections of Minimelanolocus from aquatic habitats. The genus Minimelanolocus is placed in Chaetothyriales providing molecular phylogenetic reappraisal. Four new species of Minimelanolocus are described.